Objectively measured physical activity and sedentary time of breast cancer survivors, and associations with adiposity: Findings from NHANES (2003-2006) - Lynch, B.; Dunstan, D.; Healy, Genevieve; Winkler, E.; Eakin, E.; Owen, N. (Kluwer Academic Publishers, 2010)
Objective Obesity and physical inactivity are poor prognostic indicators for breast cancer. Studies to date have relied on self-report measures of physical activity, which tend mainly to assess moderate-to-vigorous intensity leisure-time physical activity. We report the cross-sectional associations of objectively assessed physical activity and sedentary time with adiposity in a sample of breast cancer survivors from the United States. Methods One hundred and eleven women from the National Health and Nutrition Examination Survey (NHANES) 2003-2004 and 2005-2006 reported a history of breast cancer. Participants wore an accelerometer for 7 days, and activity levels were summarized as moderateto-vigorous intensity (accelerometer counts/min = 1,952), light intensity (counts/min 100-1,951), and sedentary time (counts/min <100). Anthropometric measures were taken by study staff at examination centers. Results Participants spent the majority of their day in sedentary time (66%) or in light intensity activities (33%). Log moderate-to-vigorous intensity physical activity was negatively associated with adiposity (waist circumference ß = -9.805 [95% CI: -15.836, -3.775]; BMI ß = -3.576 [95% CI: -6.687, -0.464]). Light intensity physical activity was negatively associated with adiposity; however, the fully adjusted models did not retain statistical significance. Similarly, sedentary time was positively associated with adiposity, but the fully adjusted models were not statistically significant. Conclusions This is the first study to describe the objectively assessed physical activity and sedentary time of breast cancer survivors. Increasing moderate-to-vigorous and light intensity physical activity, and decreasing sedentary time, may assist with weight management and improve other metabolic health outcomes for breast cancer survivors.